2022
DOI: 10.3390/ma15093168
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Dry Sliding Friction, Wear and Mechanical Behavior of the Ti-6Al-7Nb Alloy after Thermal Oxidation

Abstract: The mechanical and tribological characteristics of the Ti-6Al-7Nb alloy were investigated within a wide range of temperature and time parameters of thermal oxidation. The hardness, HIT, and indentation modulus, EIT, of the alloy in question, with and without an anti-wear oxide layer, were determined. The tribological properties of sliding couples were studied under technically dry friction conditions, using a ball-on-disc tribometer. The test pieces were non-oxidized and oxidized Ti-6Al-7Nb alloy discs, and Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Most of the reported work were conducted between a TO treated titanium specimen and a counter-body made of other materials, such as a ceramic, a steel and a polymer counter-body. All the reported results demonstrate that TO is effective in improving the wear resistance of titanium and its alloys by as little as 25% up to as high as 4 orders of magnitude, depending on the wear test and TO treatment conditions [12,21,27]. Some of reported tests were conducted under relatively large loads, resulting in the wearing-through of the oxide layer and even the oxygen diffusion zone [12,25,28], where the measured wear properties were not characteristic of the oxide layer and the oxygen diffusion zone, but of the composite system.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Most of the reported work were conducted between a TO treated titanium specimen and a counter-body made of other materials, such as a ceramic, a steel and a polymer counter-body. All the reported results demonstrate that TO is effective in improving the wear resistance of titanium and its alloys by as little as 25% up to as high as 4 orders of magnitude, depending on the wear test and TO treatment conditions [12,21,27]. Some of reported tests were conducted under relatively large loads, resulting in the wearing-through of the oxide layer and even the oxygen diffusion zone [12,25,28], where the measured wear properties were not characteristic of the oxide layer and the oxygen diffusion zone, but of the composite system.…”
Section: Introductionmentioning
confidence: 91%
“…All the reported results demonstrate that TO is effective in improving the wear resistance of titanium and its alloys by as little as 25% up to as high as 4 orders of magnitude, depending on the wear test and TO treatment conditions [12,21,27]. Some of reported tests were conducted under relatively large loads, resulting in the wearing-through of the oxide layer and even the oxygen diffusion zone [12,25,28], where the measured wear properties were not characteristic of the oxide layer and the oxygen diffusion zone, but of the composite system. Under light loading conditions where the oxide layer and oxygen diffusion zone were not worn-through, it has been shown that the oxide layer has extremely good wear resistance, which could be more than 2 orders of magnitude better than untreated titanium [17,21,29].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations